Late Cretaceous marine reptiles from Malyy Prolom in Ryazan Oblast, Central Russia. (November 2021) - Solonin, Sergey V.; Vodorezov, Alexey V.; Kear, Benjamin P.
Abstract: During the Cenomanian–Turonian transition (~94 Ma), what is today Central Russia formed part of the northern epicontinental margin of the Tethys Ocean. Diverse marine vertebrate faunas inhabited these palaeoenvironments, but their fossils are incompletely documented. Here, we report the discovery of marine reptile remains, recovered together with pterosaur, chondrichthyan, and actinopterygian fish material from a basal-most glauconitic sand and gravel layer of the Dmitrov Formation. These strata are exposed in an active quarry near the village of Malyy Prolom in the Shatsky District of Ryazan Oblast, Central Russia. The Dmitrov Formation deposits are middle–upper Santonian, but unconformably contact the underlying lower–middle Cenomanian Yakhroma Formation via a condensed boundary horizon that contains the vertebrate fossils with bivalve shell fragments and siliceous and phosphatic clasts. Such sedimentary characteristics indicate a high-energy shoreface setting where the vertebrate teeth and bones were likely reworked during cyclical regressions commencing in the latest Cenomanian–early Turonian. Time-averaging is also evidenced by the mixed occurrences of brachauchenine pliosaurids, elasmosaurid and polycotylid plesiosauroids, ophthalmosaurid ichthyosaurians similar to Pervushovisaurus, and a possible yaguarasaurine mosasauroid. These taxa are typical of Cenomanian–Turonian assemblages from across the northern peri-Tethys, and represent components of what were probably palaeobiogeographically widespread marine reptile faunas. Highlights: First diverse Late Cretaceous marine reptile assemblage from Central Russia. Plesiosaurs, ichthyosaurs and mosasauroids infer Cenomanian-Turonian time-averaging. Cosmopolitan relationships suggest widespread northern peri-Tethyan faunas.